Princípio de indução e aplicações - Ferreira, Luan Gomes (2018)
The history of mathematics has shown us examples of outstanding mathematicians who have made conjectures which later on were proved to be wrong from the observation of specific cases. Nowadays, not only teachers but also students can make conjectures which can be both right and wrong throughout the teach-learn-test process. Hence, the principle of mathematics induction (PMI) has been approached as a tool to check the quality of certain conjectures in the set of natural numbers.